2018
DOI: 10.1101/499293
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vaginal lubricants in the couple trying-to-conceive: assessing healthcare professional recommendations and effect on in vitro sperm function

Abstract: Tel: 07453 270117 Scott Carl Mackenzie is a medical student at the University of Dundee. Word Count: 2278 Vaginal lubricants in the couple trying-to-conceive: assessing healthcare professional recommendations and effect on in vitro sperm motility. Abstract Vaginal lubricants are commonly used by couples trying-to-conceive. However, most vaginal lubricants are sperm toxic and therefore should not be used by couples trying-to-conceive. Despite this, lubricant sperm toxicity is insufficiently reported and guidanc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…2.3.1.10 Lubricants Although commonly available, studies have demonstrated most vaginal lubricants to be detrimental to spermatozoa in vitro(Mowat et al 2014;Sandhu, et al 2014;Wilson et al 2017). Their impact on fertility and natural conception is unclear at best(Steiner et al 2012), however the use of vaginal lubricants during intercourse should not be recommended for couples with infertility unless they are able to be deemed 'Sperm safe'Mackenzie & Gellatly 2019).…”
mentioning
confidence: 99%
“…2.3.1.10 Lubricants Although commonly available, studies have demonstrated most vaginal lubricants to be detrimental to spermatozoa in vitro(Mowat et al 2014;Sandhu, et al 2014;Wilson et al 2017). Their impact on fertility and natural conception is unclear at best(Steiner et al 2012), however the use of vaginal lubricants during intercourse should not be recommended for couples with infertility unless they are able to be deemed 'Sperm safe'Mackenzie & Gellatly 2019).…”
mentioning
confidence: 99%
“…Yes and no. While no specific type of diet has reliably shown to affect fecundability, patients with a normal body mass index (BMI) are shown to have increased fecundability and a decrease in pregnancy complications [2,23].…”
Section: Diet Affects Fecundabilitymentioning
confidence: 99%